An Overview on Insect Tolerance Transgenic Crops (International Journal of Innovative Research in Engineering & Management, 2023)
Although transgenic crops have enhanced  insect pest control, their effectiveness has diminished due  to pest resistance. Humans examined global monitoring  data from the very first two decades of genetically  engineered crops, with each occurrence representing one  pest species' response to one Bacillus thuringiensis  insecticidal protein in one country (Bt). Pest tolerance to  transgenic crops' Bt crystalline (Cry) proteins has  increased from three cases in 2005 to sixteen cases in 2016.  Hereditary change that is bug-free innovation is fast growing, with enormous exploration effort in both the  commercial and legislative regions. Although the  bacterium Bacillus thuringiensis is the most widely  advertised bug-safe transgenic plant, a wide range of traits  from higher plants, particularly those producing stomach related chemical inhibitors or lectins, have also been  introduced into crop cultivars. So far, the quality of  opposition from various microbes and species has only  been used in a few circumstances.
Keywords: Bacillus Thuringiensis; Insect-Resistant; Genetic; Pesticides; Transgenic Crops